Analysing location attributes with a hedonic model for apartment prices in Donetsk, Ukraine - Kryvobokov, Marko; Wilhelmsson, Mats (International Journal of Strategic Property Management, 2010)
A hedonic model is specified for asking prices for apartments in Donetsk (Ukraine). This model is used to determine statistically significant location attributes. These attributes can be used for land assessment in a city where data on the land market are lacking. Distance gradients for CBD accessibility are investigated in different geographical directions. Separate models are created for sub‐samples located inside and outside the city centre. A spatial weight matrix is used to detect spatial autocorrelation. The regression results are compared with the valuation of experts.First published online: 18 Oct 2010